Cracking the Code: a legal geography and political ecological perspective on vegetation clearing regulations. Issue 4 (2nd October 2018) - Salgo, Matt; Gillespie, Josephine
ABSTRACT: In 2014, the New South Wales (NSW) state parliament passed legislation implementing a new Code of Practice ('Code 10/50') granting property owners in bushfire-prone areas the right to clear all trees within 10 m, and all vegetation within 50 m, of residences without prior approval from authorities. The Code is a significant departure from previous regimes which often required permits for vegetation clearance. The Code was introduced in direct response to bushfire threat in the wake of the 2013–14 bushfires in NSW. However, the Code has been plagued by controversy, with accusations of abuse in areas with little or no bushfire history, and a lack of any substantial environmental protections, particularly prior to a review in August 2015. In this paper we examine the debates surrounding the enactment of the Code and consider the way in which particular justifications for the Code permeated parliamentary deliberations. Our investigation relies on unpacking how the Code emerged in order to shed light on how a very controversial policy came into being. We adopt a legal geography approach, together with insights from political ecology, to demonstrate that changes in regulatory processes have the potential to fundamentally alter our landscapes.